THE KEY TO COMPETITIVE ADVANTAGE IN CREATIVITY AND INNOVATION MANAGEMENT IN THE DIGITAL AGE - Naylal Fithri; Moh febri; Miftahul Arifin; Ilham Jaya Kusuma; A.Rosikhon Fahmi (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study examines the role of creativity and innovation management in strengthening organizational competitive advantage in the digital era, using a literature review method that draws upon more than twenty scholarly sources published between 2019 and 2025. The findings reveal that creativity is a unique and inimitable strategic resource, serving as the primary foundation for achieving sustainable competitive advantage. Innovation, which emerges from effective creativity management, encompasses the development of new products, processes, services, and business models that enhance organizational value and competitiveness. The implementation of digital technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and Big Data has been proven to accelerate innovation and improve operational efficiency.Furthermore, an open organizational culture and innovative leadership play a crucial role in fostering a collaborative environment that encourages creativity and continuous learning. The synergy between human creativity, structured innovation, and the use of digital technology is identified as a key element in maintaining organizational competitiveness. Theoretically, the study reinforces the concepts of the Resource-Based View, Dynamic Capabilities, and Open Innovation, while practically emphasizing the importance of technology-driven creativity and innovation management supported by an adaptive and progressive organizational culture.